Agroclimatological potential of tomato (Lycopersicon lycopersicum L.) production areas - Zdeněk Žalud (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2005)
The methodology itself was based on assumption that the tomato growing areas are characterized by the certain minimum temperature sum required for the profitable production. It is obvious that the increase of the temperature predicted by the General Circulation Models will lead to the increase of these temperature sums over the whole area of the Czech Republic. However it is clear that not only meteorological elements but also suitable soil conditions are limiting factors for successful tomato growing. Therefore the presence of the predefined soil types was the second factor determining the suitability of the given region for the tomato growth. The results of the study confirmed the hypothesis that the global warming will lead to enlargement of the areas with suitable growing conditions for tomato and almost certainly for other kinds of vegetables. The changes are documented by the maps in order to identify the shifts in the distribution and extend of these areas on the district (NUTS 3) level.